2010
DOI: 10.1371/journal.pone.0010184
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Phosphorylated at Serine 45 Is Spatially Uncoupled from β-Catenin Phosphorylated in the GSK3 Domain: Implications for Signaling

Abstract: C. elegans and Drosophila generate distinct signaling and adhesive forms of β-catenin at the level of gene expression. Whether vertebrates, which rely on a single β-catenin gene, generate unique adhesive and signaling forms at the level of protein modification remains unresolved. We show that β-catenin unphosphorylated at serine 37 (S37) and threonine 41 (T41), commonly referred to as transcriptionally Active β-Catenin (ABC), is a minor nuclear-enriched monomeric form of β-catenin in SW480 cells, which express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 48 publications
8
77
0
1
Order By: Relevance
“…The phosphorylated β-catenin is then ubiquitinated by β-transducin repeatcontaining protein (β-TrCP) and subsequently degraded by the proteasome [30] ( Figure 1A). Maher et al [31] reported that β-catenin phosphorylated at Ser45 and not at Ser33/ Ser37/Thr41 is predominantly located in the nucleus, whereas β-catenin phosphorylated at Ser33/Ser37/Thr41 is mostly localized to the cytoplasm. This spatial separation of β-catenin suggests that phosphorylation at Ser45 and at Ser33/Ser37/Thr41 is not necessarily coupled.…”
Section: Overview Of Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…The phosphorylated β-catenin is then ubiquitinated by β-transducin repeatcontaining protein (β-TrCP) and subsequently degraded by the proteasome [30] ( Figure 1A). Maher et al [31] reported that β-catenin phosphorylated at Ser45 and not at Ser33/ Ser37/Thr41 is predominantly located in the nucleus, whereas β-catenin phosphorylated at Ser33/Ser37/Thr41 is mostly localized to the cytoplasm. This spatial separation of β-catenin suggests that phosphorylation at Ser45 and at Ser33/Ser37/Thr41 is not necessarily coupled.…”
Section: Overview Of Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…That being said however, the low levels of active -catenin were almost exclusively located in the nucleus. Furthermore, Maher et al, (2010) observed that -catenin phosphorylated at Thr41/Ser45 was spatially uncoupled from -catenin phosphorylated at Ser33/Ser37/Thr41. This suggested that phosphorylation at Ser45 by CK1 extended beyond a simple priming gesture (Maher et al, 2010).…”
Section: β-Catenin and The Destruction Complexmentioning
confidence: 99%
“…Furthermore, Maher et al, (2010) observed that -catenin phosphorylated at Thr41/Ser45 was spatially uncoupled from -catenin phosphorylated at Ser33/Ser37/Thr41. This suggested that phosphorylation at Ser45 by CK1 extended beyond a simple priming gesture (Maher et al, 2010). Since the majority of the Thr41/Ser45 phosphorylated -catenin translocated to the nucleus, it is entirely possible that phosphorylation at Ser45 configures an active form of -catenin (Maher et al, 2010).…”
Section: β-Catenin and The Destruction Complexmentioning
confidence: 99%
See 2 more Smart Citations